The organization of the khora in southeastern Greek Sicily: Syracuse and its hinterland (733 -598 BC) - Florenzano, Maria Beatriz Borba (Cadernos do LEPAARQ (UFPEL), 2018)
Founded by Corinthians in Sicily in the 8th century, Syracuse soon became one of the biggest and more powerful poleis of the Greek world. During the first century of life in Sicily, the Syracusans founded in the hinterland four other settlements: Heloros, Akrai, Kasmene and Kamarina. This article intends to demonstrate, through the description of material data, that: 1. These foundations were enabled thanks to negotiation with local people and that Syracusan expansion was not exclusively a military/violent one; 2. Through these foundations, Syracuse established boundaries for its initial territorial expansion; 3. The empty space between Syracuse and these boundaries were filled up by degrees and in different conditions; 4. That this movement made by Syracuse allows us to better understand an inherent characteristic of the Greek ‘way of being’, i.e., territorial control Resumo: Fundada por coríntios na Sicília, no séc. VIII a.C., Siracusa transformou-se em uma das maiores e mais poderosas pólis do mundo grego. Ao longo do primeiro século de instalados na Sicília, os siracusanos fundaram, outros assentamentos na hinterlândia: Heloros, Acrai, Casmena e Camarina. Este texto procura demonstrar, por meio da descrição da documentação material, que: 1. Estas fundações foram realizadas em negociação com as populações locais e que portanto a expansão de Siracusa não foi puramente militar e/ou violenta; 2. Por meio destas fundações Siracusa definiu os limites iniciais da expansão territorial que pretendia; 3. Que o espaço vazio entre Siracusa e esses limites foi sendo preenchido aos poucos e em graus diferentes de densidade; 4. Que este movimento de Siracusa permite que entendamos melhor um traço imprescindível do ‘modo de ser grego’, i.e, o domínio de territórios.